IMPLEMENTASI HTB (HIERARCHICAL TOKEN BUCKET) UNTUK MANAJEMEN BANDWIDTH PADA ROUTER INTERNET DI UNIVERSITAS JENDERAL SOEDIRMAN - Dwi Ary Asmoro; Hesti Susilawati; Azis Wisnu Widhi Nugraha (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2011)
HTB (Hierarchical Token Bucket) bandwidth management implementation on Jenderal Soedirman University is an improvement from PCQ (Per Connection Queue) bandwidth management. PCQ divide traffic automatically based on active users, it's weakness is in dividing a large amount of active users. The HTB impelentation refers to Mikrotik RouterOS queue tree, consists of class and parent that is filled by outgoing-interface. Each parent is adjusted based on IP adress block on each node, and determine packet-mark through IP-firewall-mangle. From the implementation result, 2 Global-total or main parent can be obtained, Unsoed down and Unsoed up. 29 Global-in or parent child down and 29 Global-out or parent child up which each parent max-limit is determined by 17,5 Mbps. The users satisfaction based independent sample t-test give the mean value of HTB browsing is 2,823 and PCQ browsing is 2,79. The mean value of HTB downloading is 2,616 and PCQ downloading is 2,636. Those values show that theres no significant differences in Unsoed internet users satisfaction. Keywords : Implementation of bandwidth, Mikrotik RouterOS, queue, parent.